Children’s self and other’s body perception : effects of familiarity and gender on how children perceive adults - Speranza, Trinidad (2022)
Fil: Speranza, Trinidad. Pontificia Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina